Ефектот од интравитреалната апликација на Бевацизумаб кај дијабетичен макуларен едем - Шекеринов, Наташа (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: Diabetic retinopathy (DR) is the most common complication associated with Diabetes mellitus (DM), and is the main reason of blindness with in the workingage population. The incidence of blindness is almost 20 times greater at people with diabetes. The leading cause of vision loss is diabetic macular edema (DME), which affects 7, 5% of the diabetics. The main precondition for the changes is the development of angiogenesis that occurs because of the release of certain angiogenic vasoproliferative factors under conditions of hypoxia and ischemic retina, reciprocally involving mechanisms of endothelial proliferation, invasion and migration for the development of pathological blood vessels Aim: To evaluate the effect of intravitreal antiangiogenic treatment (Bevacizumab Avastin®) in DME, as monotherapy and in combination with laser photocoagulation comparatively to the conventional treatment, only laser photocoagulation Design: Retrospectiveprospective, comparative, interventional study Material and Methods: The study includes patients with DM type 2, aged> 40 years with diagnosed DR and maculopathy, with present DME. Respondents had been divided in to three groups depending on the therapeutic treatment. The first group of patients (n = 60) was treated with intravitreal application of Bevacizumab 1.25mg 0, 05 ml, the second group (n = 60) with a combination treatment of Bevacizumab i. v 1.25 mg 0.05 ml and laser photocoagulation, and the control group includes patients (n = 40) treated with laser photocoagulation. In all individuals the following criteria were measured at each individual: best corrected visual acuity (BCVA) of the Snellen chart with decimal, intraocular pressuretonometry (by the Schiotz method expressed in mmHg), the slit lamp for the anterior and posterior segment with magnifier 78D (Volk). Furthermore, was used Sol. Neosynephrine 10% drops to reach mydriatic pupil, then the retina was screened with OCT (Topcon 3D2000), which allows 3D macular and retinal tissue mapping. Clinically significant parameters were HgbA1C, duration of DM, the way of its regulation, data for therapy for blood hypertension and hyperlipidemia. Results: The first group with intravitreal administration of Bevacizumab showed an improvement of VA for 0, 20 ± 0, 2; in the second group, with combined therapy, VA was improved for 0, 11± 0, 2 and in the third group with only laser, improvement of 0.09± 0, 2, and in all three groups, the pace of increase in visual acuity was registered. The average value of visual acuity related to the therapy primarily with Bevacizumab in the second group is 0, 56+ 0, 32; where primarily with laser is 0, 39+0, 2, which is statistically significant for p>0, 05. According to the dynamics index, the visual acuity after the therapy with laser was registered an increase of 5.4% compared to the previous with Bevacizumab of 43.6% After the OCT analysis, the first group had a CMT decrease of 104.0 ± 136.5 μm, with injections of 3.4 ± 0.9 on average. In the second group with average two laser interventions and 1.8 ± 0.5 injections, the reduction was 96. 3 ± μm, and in the third group CMT decreased for 52.6 μm. From the three groups, the highest percentage (70.0% and 75.0%) of patients take treatment for elevated blood pressure, and almost half of them (55. 0% and 50. 0%) use drug for hyperlipidemia, that confirms the correlation between the incidence of DM and systemic diseases, suggesting that DM is a complex metabolic syndrome. The average duration of DM in the whole group is 13.8 ± 7.0g approximately the same in all groups, ie statistically inconsequential for p <0.05 between the groups, and in correlation with the already confirmed analyzes in previous studies on the duration of diabetes and the incidence of complications, DR, for a period between 1015 years. In one patient from 120 eyes with intravitreal administration of Bevacizumab, there was a side effect, serious ocular complication, endophthalmitis. Conclusion: Continuous regression of macular edema after subsequent intravitreal applications of Bevacizumab provides visible results in improving visual acuity, and as well with significant effect on the improvement in the clinical course of DME. The therapeutic treatment with Bevacizumab itself or in combination with laser photocoagulation is more effective in treating diabetic macular edema is more effective then the conventional method, both anatomically and functionally.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Милчо Богоев.
Keywords: Diabetic macular edema (DME), anti-VEGF, Bevacizumab (Avastin®), Laser photocoagulation (LFC), Optical Coherent Tomography (OCT), Central Macular Thickness (CMT)